Embodied Social Work Practice Within Risk Society. (September 2020) - Smeeton, Joe; O'Connor, Patrick
This paper critically discusses the limitations of theorising social work from psychological and sociological perspectives and argues that phenomenology offers more opportunity to understand the embodied experiences of service users and social workers themselves. The paper argues that psychology and sociology have a limited analysis of being-in-the-world, which ought to be social work's primary consideration. The paper offers an overview of the sociology of risk before embarking on an extensive description and discussion of Heidegger's and Merleau-Ponty's phenomenology applied to the lived experience of child protection social workers working within risk society. The argument is put that phenomenology is a useful tool for understanding the lived experience of social work practitioners. Findings: The authors conclude that embodied social work practice containing fear and anxiety can be thought of as akin to taking part in extreme risk sports and that this is an unhealthy experience that is likely to skew decision-making and adversely affect the lives of social workers and service users. Applications: The authors argue that phenomenology can enhance understanding of practice and decision-making and offers insights into the lived experience of social workers. Phenomenology is useful for helping social workers negotiate risk-saturated environments, through a focus on meaning.